Genetic Disorders: Clinical Aspects - Stanton, L. Luke (Hayle medical, 2018)
The disorder caused by any abnormality found in an individual's genes is known as a genetic disorder. They are mostly hereditary or can also be caused by new mutations. Genetic disorders can be grouped into three types - single gene disorders, chromosome disorders and multifactorial disorders. With advanced research and technology, new approaches are being developed in treating genetic disorders. This book presents the complex subject of genetic disorders in the most comprehensible and easy to understand language.